A promising approach to effectively reduce cramp susceptibility in human muscles: a randomized, controlled clinical trial. - Michael Behringer; Markus Moser; Molly McCourt; Johannes Montag; Joachim Mester (PLoS ONE)
Background To investigate if the cramp threshold frequency (CTF) can be altered by electrical muscle stimulation in a shortened position. Methods A total of 15 healthy male sport students were randomly allocated to an intervention (IG, n = 10) and a non-treatment control group (CG, n = 5). Calf muscles of both legs in the IG were stimulated equally twice a week over 6 weeks. The protocol was 3×5 s on, 10 s off, 150 µs impulse width, 30 Hz above the individual CTF, and was at 85% of the maximal tolerated stimulation energy. One leg was stimulated in a shortened position, inducing muscle cramps (CT), while the opposite leg was fixated in a neutral position at the ankle, hindering muscle cramps (nCT). CTF tests were performed prior to the first and 96 h after the 6(th) (3 w) and 12(th) (6 w) training session. Results After 3 w, the CTF had significantly (p<0.001) increased in CT calves from 23.3±5.7 Hz to 33.3±6.9 Hz, while it remained unchanged in nCT (pre: 23.6±5.7 Hz, mid: 22.3±3.5 Hz) and in both legs of the CG (pre: 21.8±3.2 Hz, mid: 22.0±2.7 Hz). Only CT saw further insignificant increases in the CTF. The applied stimulation energy (mA² • µs) positively correlated with the effect on the CTF (r = 0.92; p<0.001). Conclusions The present study may be useful for developing new non-pharmacological strategies to reduce cramp susceptibility. Trial registry German Clinical Trials Register DRKS00005312.